Design and Validation of Multimodal Project-Based Learning Syntax for Prospective Physics Teachers - Gunawan Gunawan; Ahmad Harjono; Muhammad Zuhdi; Jannatin Ardhuha; Nina Nisrina; Windy Zaerani; Shelliana Iqlima (Department of Physics Education, Universitas Mataram, 2026)
Physics education in the digital era demands pre-service teachers to be proficient in packaging abstract concepts into cognitive-friendly, multimodal digital media. However, conventional Project-Based Learning (PjBL) models frequently remain final product-oriented, lacking explicit guidance on content representation. This study aims to describe the conceptual design process of the Multimodal-PjBL syntax for pre-service physics teachers and to evaluate its theoretical feasibility. The research adopted a Research and Development (R&D) approach using the ADDIE model, which was limited to the first three phases up to expert validation. Data were collected utilizing a 5-point Likert scale expert validation instrument evaluating content accuracy, structural construct, readability (language), and technical presentation of the Model Book, instructional kits, and supporting research instruments. The research subjects involved four expert validators (two content specialists and two media specialists). Quantitative data were analyzed using a five-point mean score conversion interval, while qualitative data were processed interactively through data reduction and a revision tracking matrix. The results revealed that the structural modification of the PjBL syntax was successfully and logically integrated with multimodal aspects across all instructional stages. Quantitatively, all developed documents achieved a